Evaluación técnico financiera del empaquetamiento revestido con grava para el control de arena del Pozo T1 del Campo La Cira Infantas (2018)
At present, in the La Cira Infantas Field, sand production is handled on the surface and through interventions for its accumulation in the wells, this significantly affects the performance of the bottom and surface equipment as well as increasing costs by intervention in the countryside. This project sought to evaluate technically and financially the packaging covered with gravel in Well T1. For this, a historical review of the well, its production, completion and number of interventions related to problems by sandblasting was made. Then with the data of the granulometric analysis provided by the company Occidental de Colombia, the mesh size needed to exercise an effective control of the sand was selected, later and through the PROSPER simulator the nodal analysis was obtained for the current state of the well and for the sand control system proposed, in this way it was possible to compare the production of oil in both cases and the analysis of sand production was carried out, in addition to presenting different sensitivities to evaluate possible completion scenarios. Finally, an evaluation of the financial viability of the project was carried out through the use of the Net Present Value (NPV) methodology, analyzing the investment, operation and maintenance costs of the current state of Well T1 as well as of the possible when packaging is used.